The price of remoteness: Product availability and local cost of living in Ethiopia - Julien Martin; Florian Mayneris; William Theophile Ewane (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2024)
We use the microdata underlying the Ethiopian CPI to examine the spatial dispersion in local prices and availability of 401 items across 106 cities. Remote cities face higher prices and have access to fewer products. Large cities also face higher individual prices but enjoy access to a wider set of products. To assess the welfare implications of these patterns, we aggregate the data and build spatial cost-of-living indexes that account for both the price of available products and product availability. The cost of living is higher in remote and large cities. Moving from the first to the ninth decile in terms of remoteness (holding population size constant) results in an 8.3% increase in the cost of living. A comparable move in terms of population size (holding remoteness constant) leads to a 3.7% increase in the cost of living.
Keywords: 330; Verbraucherpreisindex; Regionaler Preisindex; Produkt; Periphere Region; Binnenwanderung; Äthiopien